USING INTERACTIVE AND PEDAGOGICAL METHODS IN TEACHING MATHEMATICAL LESSONS (Web of Technology: Multidimensional Research Journal, 2024)
This article provides information about modern methods that are most often used in primary mathematics classes. Methods of application of these methods and their effectiveness are discussed.